MarTech - Bilro, R.G. (International Encyclopedia of Business Management, 2026)
Marketing Technology (MarTech) revolutionizes the integration of technology and marketing, transforming customer engagement through advanced tools and strategies. By leveraging technologies like artificial intelligence (AI), extended reality (XR), the Internet of Things (IoT), and blockchain, MarTech enhances personalised, data-driven decision-making and customer experiences. Its adaptability enables precision targeting, multi-channel consistency, and real-time interactions, exemplified by innovations such as chatbots and predictive analytics. MarTech drives efficiency, fosters innovation, and provides a competitive edge through unique marketing solutions, making it vital in today’s evolving marketplace. Scalable for businesses of all sizes, it empowers organisations to meet customer needs with precision while achieving strategic growth in a dynamic digital landscape.